Impedimento de un régimen semiabierto y abierto a los delitos en contra de la administración publica tipificados en el Art 113 y 114 de la Ley Orgánica Reformatoria al Código Orgánico Integral Penal - Crespo Icaza, Marcos Josué (2023)
This investigation that has as its title: The impediment of a semi-open and open regime of crimes against the efficient Public Administration typified in articles 113 and 114 of the Organic Law Reformatory to the COIP. The same that was promulgated in the Official Registry on December 20, 2019, reforming Articles 698 and 699 of the COIP regulations that previously did not prohibit social rehabilitation regimes regardless of the type of crime for which they have been sentenced. This investigative work aims to analyze in comparative law if the crimes of embezzlement, bribery, extortion and illicit enrichment cannot access prison benefits, as well as to determine the disadvantages brought about by the prohibition of this criminal subrogation where the principle of proportionality, right to equality, rationality and criminal guarantee................